Bimbingan Kelompok Untuk Meningkatkan Minat Belajar Siswa Kelas VII.E SMP Negeri 1 MENGWI Tahun Ajaran 2024/2025 - Made Dwi Udiani; Putu Agus Giri (Journal Prakarsa Paedagogia, 2025)
Low learning interest among students is a significant factor hindering optimal academic achievement. This study aims to enhance students' learning interest through the implementation of group counseling using group discussion techniques with seventh-grade students (VII.E) at SMP Negeri 1 Mengwi, Academic Year 2024/2025. This research employs a Counseling and Guidance Action Research (PTBK) approach, conducted in two cycles. The subjects of this study were 8 students exhibiting low learning interest out of 36 total students. The results indicate that in Cycle I, learning interest improved, with scores ranging from 112 to 120 (moderate category), corresponding to 56%-60%. In Cycle II, further improvement was observed, with scores ranging from 152 to 160 (high category), or 76%-80%. Overall, the increase in learning interest was 34.03%. These findings suggest that group counseling with group discussion techniques is effective in enhancing students' learning interest. It is recommended that school counselors integrate this approach into their practices to support the optimal development of students' potential.